Does Knowledge Stickiness Affect a Firm’s Innovation Capability? Empirical Evidence From Indonesian Furniture SMEs - Nurul Indarti (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
This study aims to examine the relationship between knowledge stickiness and a firm’s innovation capability in the context of developing countries, i.e., Indonesia. The main research question addressed by this study is: does knowledge stickiness affect a firm’s innovation capability? Using data from 100 small- and medium-sized furniture enterprises (SMEs), the study finds that product innovations are predominant over process and organizational ones. However, incremental innovations are often more preferred than radical ones. This study also finds that the firms absorb knowledge from various sources to undertake innovations. Buyers, Internet, and suppliers are the significant sources, for sensory, coded, and theoretical knowledge. Buyers are also the main source of a great extent of various knowledge domains related to product, process, and organizational innovations. In general, the furniture firms do not pay considerable attention to planning stages when introducing innovations, as indicated by the fact that not all innovations are preceded by initiatives, except for really new processes and organizational innovations whose impact on the firms’ revenue is less visible. Out of four dimensions of knowledge stickiness used in this study, three of them (i.e., knowledge interconnectedness, sensory knowledge, and coded knowledge) are proven to have significant impact on a firm’s innovation capability. We find, knowledge interconnectedness and coded knowledge have a positive impact, while sensory knowledge influences a firm’s innovation capability in a negative direction. All in all, this study provides empirical evidence that knowledge stickiness has a significant impact on a firm’s innovation capability (explains 36% of total variance).